2023
DOI: 10.3390/rs15092316
|View full text |Cite
|
Sign up to set email alerts
|

Accurate Retrieval of the Whole Flood Process from Occurrence to Recession Based on GPS Original CNR, Fitted CNR, and Seamless CNR Series

Abstract: The CNR (Carrier-to-Noise Ratio) of GPS (Global Positioning System) satellites is highly relevant to the multipath error. The multipath error is more serious in the flood environment since the reflection and diffraction coefficients of water are much higher compared to dry soil. Thus, the amplitude of CNR will decrease in the flood environment. In this study, the relationship between multipath error, flooding, and CNR is introduced in theory. Then, by using the characteristic of the orbital repetition period, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…Similar methods can also be found in Strode and Groves [15], Zhang et al [16], and Su et al [8]. Considering that the multipath error performs more seriously during the flood, Su et al investigated the influence of flood on the CNR of GPS satellites, the results indicate that the CNR during the flood performs lower than that without flood [17,18]. In addition, Su et al demonstrated that not only the CNR of GPS satellites was affected during the flood, but also the CNR of GLONASS satellites [11].…”
Section: Introductionmentioning
confidence: 61%
“…Similar methods can also be found in Strode and Groves [15], Zhang et al [16], and Su et al [8]. Considering that the multipath error performs more seriously during the flood, Su et al investigated the influence of flood on the CNR of GPS satellites, the results indicate that the CNR during the flood performs lower than that without flood [17,18]. In addition, Su et al demonstrated that not only the CNR of GPS satellites was affected during the flood, but also the CNR of GLONASS satellites [11].…”
Section: Introductionmentioning
confidence: 61%
“…SNR is a measurement parameter representing the strength quality of a signal received from the receiver antenna, including the direct and the reflected signals [39,58,59]. At any time, the SNR is a function of direct power, reflected power, and the phase difference between them.…”
Section: Gnss Satellite Reflected Signalmentioning
confidence: 99%